Hydrogenation of p-nitrophenol by gold nanoparticles immobilized within macroporous amphoteric cryogel based on N,N-dimethylaminoethylmethacrylate and methacrylic acid - Klivenko, A.N.; Tatykhanova, G.S.; Nuraje, Nurxat; Kudaibergenov, S.E. (KSU Publ., 2015)
Macroporous amphoteric cryogel based on N,N-dimethylaminoethylmethacrylate and methacrylic acid (DMAEM-MAA) was used for immobilization of gold nanoparticles (AuNPs). The structure of AuNPs immobilized within macroporous amphoteric cryogel represents the triangular, hexagonal, spherical and rod-like species the sizes of which are varied from 3 to 10 μm. Amphoteric cryogel with immobilized AuNPs was tested as flow-through catalytic reactor in reduction of 4-nitrophenol by NaBH4.
Алтынның нанобөлшектері иммобилденген N,N-диметиламиноэтилметакрилат жəне метакрил қышқылы негізіндегі макроторлы амфотерлі криогель көлемінде п-нитрофенолды гидрлеу
Гидрирование п-нитрофенола наночастицами золота, иммобилизованными в макропоры амфотерного криогеля на основе N,N-диметиламиноэтилметакрилата и метакриловой кислоты
Keywords: macroporous amphoteric cryogels; gold nanoparticles; catalytic activity; flow-through reactor